The effect of a one-piece competition speedsuit on swimming performance and thermoregulation during a swim-cycle trial in triathletes - Peeling, P.; Landers, G. (Journal of Science and Medicine in Sport, 2007)
This study investigated the thermoregulatory response to wearing a one-piece competition speedsuit during the swim-cycle aspect of a sprint-distance triathlon. Eight highly trained, male triathletes completed a graded-exercise test, and two swim-cycle trials including a 750 m swimming time trial followed by 30 min of cycling at 95% lactate threshold. Cycling was conducted inside a climate regulated chamber set to 30.0+/-0.3 degrees C and 60.3+/-0.3% humidity. Throughout each swim-cycle testing session, the athletes wore either standard swimming bathers only (BATHERS), or a competition speedsuit (SPEEDSUIT). During the swim-cycle trial, the athletes core temperature (T(c)) and skin temperature (T(sk)) were recorded via a telemetric temperature pill and a series of skin thermistors, respectively. Blood lactate concentration (BLa), heart rate (HR) and ratings of perceived thermal sensation (RPTS) were collected at the conclusion of the swim and during cycling. The SPEEDSUIT swim time (590+/-20s) was significantly faster (3.2%, p<0.01) than the BATHERS trial (609+/-24s). This time improvement incurred no between group differences in T(c), BLa or RPTS (SPEEDSUIT: 38.4+/-0.2 degrees C, 8.3+/-0.9 mmol L(-1), 15+/-1, BATHERS: 38.2+/-0.1 degrees C, 8.4+/-1.1 mmol(-1), 15+/-1, respectively) (p>0.05). During the 30 min cycle, there were not significant differences between the mean values for power output, T(c), T(sk), HR, BLa or RPTS (SPEEDSUIT: 289+/-13W, 38.65+/-0.27 degrees C, 34.30+/-0.71 degrees C, 7.8+/-1.1 mmol L(-1), 17+/-1, BATHERS: 288+/-14W, 38.35+/-0.10 degrees C, 33.50+/-0.57 degrees C, 7.1+/-0.9 mmol L(-1), 17+/-1, respectively) (p>0.05). The use of a competition speedsuit improved the triathletes' swim time without effecting temperature regulation during a laboratory-based swim-cycle trial.